(untitled) - Balagot, Beta P. (Halifax, N.S., 1994)
The goal of ERMP is to help UPLB strengthen its capability to contribute to environemt and resource management in the Philippines.
Keywords: Environmental impact analysis,Environmental policy; Philippines,Philippines